The Effect of the Application of the Jigsaw Type Cooperative Learning Model on the Motivation to Learn Applied Physics Courses at the Merchant Marine Polytechnic of Makassar Cadets - Agustina Setyaningsih (International Journal of Social Service and Research, 2023)
This research is a quantitative-research using an experimental approach. The type of research used is experimental research. The objectives of this study are (1) to determine the significant effect of the jigsaw cooperative learning model on the motivation to learn Applied Physics for cadets at the Merchant Marine Polytechnic of Makassar, (2) to determine the effect of the level of motivation before and after using the jigsaw cooperative learning model. The research was carried out at the Merchant Marine Polytechnic of Makassar from April to September 2022. The population in this study were all cadets of the Engineering Study Program semester II for the Academic Year 2021/2022 at the Merchant Marine Polytechnic of Makassar, totaling 48 cadets. Data collection techniques using a questionnaire. The data analysis technique used normality test, correlation test, homogeneity test, and test of difference in average value (t test). The results showed that the application of the Jigsaw learning model had a significant effect on the motivation to learn applied physics for cadets at the Merchant Marine Polytechnic of Makassar with a correlation coefficient of 0.436. Furthermore, there are differences in the level of learning motivation in the control class and the experimental class. The learning motivation in the control class is in the medium category while the experimental class is in the high category.